Should Hybrids Be Used in Coral Nurseries? A Case Study Comparing Caribbean Acropora spp. and Their Hybrid in the Bahamas - VanWynen, Cassie M.; Hightshoe, Morgan V.; Fogarty, Nicole D.; Dahlgren, Craig P.; Gilliam, David S. (Frontiers in Marine Science, 2021)
For decades, coral reef ecosystems have been in decline due to environmental stressors such as rising sea temperatures, increased disease prevalence, and other local anthropogenic sources. Considering this decline, coral restoration efforts in the Caribbean have been implemented to promote reef recovery with a focus on the coral genus Acropora. Current methods target the threatened species Acropora cervicornis and A. palmata, but little is known about the restoration potential of their hybrid taxon, A. prolifera. Using interspecific hybrids with higher fitness than one or both parental species has gained traction as a novel restoration technique. For this study, three in situ coral tree nurseries were established around Great Stirrup Cay, The Bahamas, to compare the growth and survival among acroporid taxa. Three 150 mm fragments from six putative genotypes of each acroporid taxa were collected from reefs around New Providence, The Bahamas, and transported to Great Stirrup Cay in June 2018. One fragment from each genotype was transported to each nursery site, cut into three sections (apical, middle, and basal), and suspended from PVC coral trees. Fragment survival was collected monthly for 13 months, and Total Linear Extension (TLE) values were calculated for each fragment monthly for 12 months. Nursery site significantly affected fragment survival, while taxon and fragment section did not. Total fragment mortality was 29.3% in the first month but ranged from 0 to 5% for the rest of the study period until July 2019 (32.7% of remaining fragments died primarily at N1). Overall, A. prolifera growth was significantly greater than the parental species. Taxon, nursery site, and fragment section were identified as important factors affecting TLE. Apical A. prolifera fragment sections at site N3 had the greatest average linear growth at 12 months and had the greatest average growth rate per month. This study highlights the rapid growth rate of hybrid corals and suggests that fragment sections have equivalent survival and growth. Consequently, these results suggest that restoration managers may capitalize on fast growing hybrids for outplanting to degraded reefs and to increase the scale of nursery projects.